1992
DOI: 10.1007/bf01063291
|View full text |Cite
|
Sign up to set email alerts
|

A farm-level evaluation of nitrogen and phosphorus fertilizer use and planting density for pearl millet production in Niger

Abstract: Mineral fertilizer use is increasing in West Africa though little information is available on yield response in farmers' fields. Farmers in this region plant at low density (average 5,000 pockets h a-1, 3 plants pocket-1), which can affect fertilizer use efficiency. A study was conducted with 20 farmers in Niger to assess the response of pearl millet [Pennisetum glaucum (L.) R. Br.] to phosphorus and nitrogen fertilizers under farm conditions. In each field, treatments included control, single superphosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 9 publications
(3 reference statements)
0
44
0
Order By: Relevance
“…There is no positive response to N unless adequate P is supplied (Buerkert and Stern, 1995;Buerkert et al, 2001). There were many research works done to prove the beneficial effect of N and manly P fertilizer in the area (e.g., Christianson et al, 1990;Bationo et al, 1992;Subbarao et al, 2000;Bationo and Ntare, 2000;Buerkert et al, 2001;Yamoah et al, 2002). Single superphosphate (SSP) applied annually at 13 kg P ha -1 effectively removed P deficiency on most cases.…”
Section: Mineral Fertilizermentioning
confidence: 99%
“…There is no positive response to N unless adequate P is supplied (Buerkert and Stern, 1995;Buerkert et al, 2001). There were many research works done to prove the beneficial effect of N and manly P fertilizer in the area (e.g., Christianson et al, 1990;Bationo et al, 1992;Subbarao et al, 2000;Bationo and Ntare, 2000;Buerkert et al, 2001;Yamoah et al, 2002). Single superphosphate (SSP) applied annually at 13 kg P ha -1 effectively removed P deficiency on most cases.…”
Section: Mineral Fertilizermentioning
confidence: 99%
“…Given the low soil fertility and the lack of use of mineral fertilizers, planting densities are very low, usually around 5000 planting hills (pockets) ha -1 or even lower (Bationo et al, 1992;Mclntire, 1986).…”
Section: Environmental Conditions and Land Usementioning
confidence: 99%
“…The major constraints to arable agriculture are crop growth on the predominantly sandy soils that are of poor soil fertility; particularly in phosphorus (P) and nitrogen (N) (Bationo et al, 1992;1993;1998a;b); It has, however, been reported that phosphorus tends to be more limiting to crop productivity than nitrogen. Crop response to nitrogen was found to be minimal until crop phosphorous requirements had been satisfied (Traore, 1974).…”
Section: Introductionmentioning
confidence: 99%